Evidence of a Continuous Continental Permian-Triassic Boundary Section in western Equatorial Pangea, Palo Duro Basin, Northwest Texas, U.S.A. - Tabor, Neil J.; Geissman, John; Renne, Paul R.; Mundil, Roland; Mitchell, William S.; Myers, Timothy S.; Jackson, Jacob; Looy, Cindy V.; Kirchholtes, Renske P. (Frontiers in Earth Science, 2022)
The Whitehorse Group (WG) and Quartermaster Formation (QF) are extensive red-bed shallow marine and terrestrial sequences representing the final episode of sedimentation in the Palo Duro Basin, west Texas, U.S.A., and record the culmination of a long term regression sequence beginning in the Middle Permian. The WG includes abundant laminated to massive red quartz siltstone to fine sandstone and rare dolomite, laminated to massive gypsum, and claystones. The QF has nearly equal amounts of thin planar and lenticular fine sandstone and laminated to massive mudstone in its lower half to overlying strata with coarser-grained, cross-bedded sandstones and rare overbank mudstones. Paleosols are absent in the upper WG and only poorly developed in the QF. Volcanic ash fall deposits (tuffs) in uppermost WG and lower QF strata provide geochronologic age information for these rocks. Single zircon U-Pb CA-TIMS analyses from at least two distinct volcanic ash fall layers in the lower QF, from five localities across the basin, yield interpreted depositional ages ranging from 252.19 ± 0.30 to 251.74 ± 0.28 Ma. Single zircon U-Pb CA-TIMS analyses of detrital zircons from sandstones a few meters beneath the top of the QF yield dates from Mesoproterozoic (1418 Ma) to Middle Triassic (244.5 Ma; Anisian), implying that the PTB lies within the lower QF/upper WG succession. Stable carbon isotope data from 180 samples of early-burial dolomicrite cements preserve a chemostratigraphic signal similar among sections, with a large ~-8‰ negative isotope excursion ~20 m beneath the WG-QF boundary. This large negative carbon isotope excursion is interpreted to be that associated with the end-Permian extinction, consistent with the new age data and the fact that the excursion lies within a normal polarity stratigraphic magnetozone, Dolomite cement δ13C values remain negative into the lower part of the QF before becoming more positive upward. This long interval of negative δ13C values in the QF is interpreted as the Induan inception of biotic and ecosystem “recovery”. The paleoenvironment and paleoclimate across the PTB in western, sub-equatorial Pangea were harsh for life and not conducive to a rich biodiversity, even with evidence for an abundance of relatively fresh water.